Four cases of pediatric deep‐seated/subcutaneous pyogenic granuloma: Review of literature and differential diagnosis. (23rd March 2017) - Putra, Juan; Rymeski, Beth; Merrow, Arnold C.; Dasgupta, Roshni; Gupta, Anita
Abstract : Background: Pyogenic granulomas are benign, reactive, typically superficial vascular lesions that can be idiopathic or arise secondary to trauma, underlying vascular malformations, infections, physiologic or pathologic endocrine changes, and hormone therapy. Deep‐seated/subcutaneous pyogenic granulomas (DSPG) are rarely seen in any age group. Pediatric DSPGs can be a clinical and pathologic challenge because these lesions mimic other vascular lesions, including kaposiform hemangioendothelioma, infantile hemangiomas and vascular malformations. Methods: Retrospective search of DSPG excised at Cincinnati Children's Hospital Medical center between June 2010 and June 2011 was conducted. Clinical information was obtained from patient charts and histologic slides were retrieved and reviewed. Results: Of the 106 cases of pyogenic granuloma, 4 (3.8%) were diagnosed as DSPG. We report the details of those 4 cases and compare them with the other pediatric DSPG cases reported in the literature. We also review the histologic differential diagnosis of DSPG in pediatric population. Conclusion: Our results suggest that these lesions may not be as rare as inferred by literature, but, rather, underdiagnosed.